Penerapan Teorema Probabilitas Total dalam Analisis Resiko Gempa - Wahyono, M.; Nurdin, S.; Bedu, A.; Eko, W.N.; Sari, R.N. (Civil Engineering Department, Tadulako University, 2020)
Total probabilistic theorem was applied to analyze seismic risk by mean Probabilistic Seismic Hazard Analysis (PSHA). Earthquake as natural earthquakes as a random natural event was approached by the concept of uncertainty. The PSHA method is described in 5 (five) stages of work, called identificating the source of the earthquake, characterizing the earthquake source, characterizing the seismicity, determinating the movement of soil surface occurring at a location due to the earthquake, the combining the uncertainty of the location of the earthquake, magnitude of the earthquake and prediction of soil surface movement parameters. Ez-Frisk computer Program was used to perform earthquake risk calculation. Earthquake risk analysis for the city of Bontang, East Kalimantan taken as a case study. Peak Ground Acceleration (PGA) in Bontang base rocks for some periodic of time presented in chart form as result of earthquake risk analysis.